Penerapan Teknik Cutout Rigging pada Pembuatan Karakter Animasi 2D "Luka Lama Lautan" Sebagai Media Edukasi SDGS 14: Life Below Water - Ghazi Fadhlurrahman Siddiq; Nurmaya Prahatmaja; Andri Yanto (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
The development of digital technology has encouraged the emergence of various educational media that are capable of delivering information in a more engaging and understandable way. Generation Alpha, as a generation that grows up in a digital environment, tends to be more responsive to visual and audiovisual media than to conventional methods of information delivery. Therefore, animation is considered an effective educational medium because it combines visual elements, motion, audio, and storytelling, allowing messages to be communicated more effectively to the audience. This final project is a 2D animation entitled "Luka Lama Lautan" (The Ocean's Old Wound), which addresses the issue of marine pollution caused by plastic waste as an educational medium related to environmental awareness. In the production process, the author acts as the animator and is responsible for designing and animating the characters using cutout rigging techniques. The techniques applied include layering, parenting, anchor point adjustment, deformation using the Puppet Tool, and keyframe animation in Adobe After Effects. The implementation of cutout rigging techniques aims to support production efficiency while producing more communicative character movements in delivering educational messages to the audience. The resulting animation is presented using a vector-based animation style with colorful and expressive visuals that are adapted to the preferences of Generation Alpha. In addition, the main character is designed with inspiration from digital culture trends that are familiar to the target audience, creating a stronger emotional connection with viewers. Through the combination of engaging visuals, communicative character movements, and a simple narrative approach, the animation is expected to function not only as entertainment but also as an effective educational medium that helps increase children's awareness of the importance of protecting the marine environment.